Contribuiç\~oes do programa de aquisiç\~ao de alimentos para a segurança alimentar e nutricional no Brasil - Regina Helena Rosa Sambuichi; Iracema Ferreira De Moura; Juliana Gonçalves Machado; Gabriela Perin (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
The Food Acquisition Program (PAA) is a public policy that uses the federal government's purchasing power to promote the strengthening of family farming and combat food and nutritional insecurity in Brazil. This text presents an analysis of PAA acquisitions in the period from 2011 to 2019 to discuss the program's contributions to food and nutritional security (SAN) and debate its future perspectives. It was found that the program acquired a wide variety of products, including food and seeds, with 1,211 different items purchased in the period. Among the foods purchased, there was a predominance of fresh and minimally processed classes, which together accounted for 97.1% of purchases. The Purchase with simultaneous donation modality was responsible for most of the purchases (57.5% of the quantity and 93% of the variety) and its purchases were mainly represented by the groups of fruits and vegetables. The results indicated that the food purchased by the PAA is in accordance with the guidelines of the Food guide for the brazilian population for an adequate and healthy diet, contributing not only to the health and food safety of its direct beneficiaries, but also to the promotion of a more sustainable food system. However, there was a drastic reduction in the amounts invested in purchases over the period analyzed, which could compromise the program's ability to generate these benefits. In addition, there have been recent changes in legislation in this public policy, which, in addition to changing the name of the program, left out some important points contained in its previous regulations. Therefore, to ensure continuity of its benefits, it is recommended that all the specificities contained in the previous regulations be rescued in the new legislation and, mainly, that more resources be made available again for the purchases of the program.
Keywords: Q18; 330; family farming; public policies; food security and nutrition